2011
DOI: 10.1038/cmi.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms and graft-versus-host disease in children after matched sibling hematopoietic stem cell transplantation: a single-center experience

Abstract: Various polymorphisms in cytokine genes have recently been investigated as candidate risk factors in allogeneic hematopoetic stem cell transplantation (allo-HSCT). We retrospectively analyzed specific polymorphisms in genes for interleukin (IL)-10, IL-6, tumor-necrosis factor alpha (TNF-a) and interferon gamma (IFN-c) in a pediatric cohort of 57 histocompatibility leucocyte antigen (HLA)-identical sibling myeloablative transplants. Both recipient and donor genotypes were tested for association with graft-versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
1
17
1
Order By: Relevance
“…Interestingly, the latter results do not corroborate with the literature findings [5,11,12]. Nonetheless, increased secretion of IL-10 (GCC haplotypes) promotes the differentiation, proliferation and antibody production of B lymphocytes [22][23][24]. Moreover, a body of evidence has accumulated indicating that IL-10 can have pleiotropic effects on adaptive and innate immunity cell mediators as well as a protective role from autoimmune diseases [25].…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the latter results do not corroborate with the literature findings [5,11,12]. Nonetheless, increased secretion of IL-10 (GCC haplotypes) promotes the differentiation, proliferation and antibody production of B lymphocytes [22][23][24]. Moreover, a body of evidence has accumulated indicating that IL-10 can have pleiotropic effects on adaptive and innate immunity cell mediators as well as a protective role from autoimmune diseases [25].…”
Section: Discussionmentioning
confidence: 81%
“…Three common haplotypes represent high (GCC), intermediate (ATA) and low (ACC) IL‐10 production (Suarez et al , ). As one might expect, the presence of the high‐producing (GCC) haplotype in HCT recipients correlated with decreased risk for aGVHD (Karabon et al , ; Goussetis et al , ). Contrary results were reported in one large study, however, that found the presence of recipient or absence of donor GCC haplotype increased risk for GVHD (Socie et al , ).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…A large body of research literature has shown links between chronic and acute stress and short-or long-term psychological and physical disorders, such as anxiety, depression, and PTSD (5)(6)(7). Specifically, people who experience a large number of stressors related to infectious diseases tend to show more psychological symptoms (e.g., PTSD, depression) than those who experience fewer stressors (6,8). The COVID-19related stressors are those stressful events related with COVID-19 disease that might endanger their well-being, such as an important person being infected with COVID-19 or having to cancel a vacation due to the pandemic.…”
Section: Relation Of Stress To Psychological Responsementioning
confidence: 99%